Acoustic turbidity as online monitoring tool for rivers and sewer networks. (April 2016) - Pallarès, A.; Fischer, S.; France, X.; Pons, M.N.; Schmitt, P.
Abstract: This paper focuses on the use of the raw acoustical turbidity and velocity data as a flow online monitoring tool. Its aim is to demonstrate that, with adequate instrumental settings, interesting results can directly be seen on the raw data. As illustration, some experimental results on a combined acoustic turbidity and velocity analysis on a river are shown. It demonstrates the great potential of the acoustic measurements in sediment transport studies by the combined information on velocity and turbidity. Another application is the study of a wastewater collector inlet for which the comparison with standard measurement methods is possible. The acoustic turbidity raw data can easily be used for qualitative suspended solids concentration studies. It is also shown that more accurate results on the water height can be obtained through the acoustic turbidity. Highlights: Use of the raw acoustic turbidity and velocity data for the survey of water flows. Observations on river and wastewater show that the use of the raw acoustic turbidity, without inversion, and velocity data can already give interesting results. Comparison with standard techniques in wastewater showed good agreement and gives advantage to the acoustic data.